Bovine In Vitro Oocyte Maturation and Embryo Production Used as a Model for Testing Endocrine Disrupting Chemicals Eliciting Female Reproductive Toxicity With Diethylstilbestrol as a Showcase Compound - Asimaki, K.; Vazakidou, P.; van Tol, H. T. A.; Oei, C. H. Y.; Modder, E. A.; van Duursen, M. B. M.; Gadella, B. M. (Frontiers in Toxicology, 2022)
Endocrine disrupting chemicals (EDCs) can interfere with normal hormonal action and regulation. Exposure of women to EDCs has been associated with adverse reproductive health outcomes. The assays currently used to identify EDCs that elicit female reproductive toxicity lack screening tests that address effects on the maturation of oocytes, a process that enables them to be fertilized and develop into embryos. Here, a screening method employing the bovine model of in vitro oocyte maturation and embryo production is described. Endpoints explored address important events in oocyte maturation and developmental competence acquisition. To test the method, the effects of the known human EDC diethylstilbestrol (DES; an estrogen receptor agonist) were evaluated in a range of concentrations (10-9 M, 10-7 M, 10-5 M). Bovine oocytes were exposed to DES during in vitro maturation (IVM) or embryos were exposed during in vitro embryo culture (IVC). The endpoints evaluated included nuclear maturation, mitochondrial redistribution, cumulus cell expansion, apoptosis, and steroidogenesis. DES-exposed oocytes were fertilized to record embryo cleavage and blastocyst rates to uncover effects on developmental competence. Similarly, the development of embryos exposed to DES during IVC was monitored to assess the impact on early embryo development. Exposure to 10-9 M or 10-7 M DES did not affect the endpoints addressing oocyte maturation or embryo development. However, there were considerable detrimental effects observed in oocytes exposed to 10-5 M DES. Specifically, compared to vehicle-treated oocytes, there was a statistically significant reduction in nuclear maturation (3% vs. 84%), cumulus expansion (2.8-fold vs. 3.6-fold) and blastocyst rate (3% vs. 32%). Additionally, progesterone and pregnenolone concentrations measured in IVM culture media were increased. The screening method described here shows that bovine oocytes were sensitive to the action of this particular chemical (i.e. DES), albeit at high concentrations. In principle, this method provides a valuable tool to assess the oocyte maturation process and early embryo development that can be used for reproductive toxicity screening and possibly EDC identification. Further studies should include EDCs with different mechanisms of action and additional endpoints to further demonstrate the applicability of the bovine oocyte model for chemical risk assessment purposes and EDC identification.